2011
DOI: 10.1016/j.annemergmed.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Missed Opportunities for Earlier HIV Diagnosis in 3 Geographically Proximate Emergency Departments

Abstract: Objective Differences in the prevalence of undiagnosed HIV between different types of emergency departments (EDs) are not well understood. We seek to define missed opportunities for HIV diagnosis within 3 geographically proximate EDs serving different patient populations in a single metropolitan area. Methods For an urban academic, an urban community, and a suburban community ED located within 10 miles of one another, we reviewed visit records for a cohort of patients who received a new diagnosis of HIV betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
3
24
1
Order By: Relevance
“…Our results may not be generalizable to centers with different epidemiology; EDs differ in terms of disease prevalence even in the same region, 78,79 and EDs are certain to differ from other healthcare venues. 10,19 Our study was strengthened by controlling overall screening methodology to isolate differences resulting from patient selection strategy.…”
Section: Discussionmentioning
confidence: 63%
“…Our results may not be generalizable to centers with different epidemiology; EDs differ in terms of disease prevalence even in the same region, 78,79 and EDs are certain to differ from other healthcare venues. 10,19 Our study was strengthened by controlling overall screening methodology to isolate differences resulting from patient selection strategy.…”
Section: Discussionmentioning
confidence: 63%
“…Lyons et al 66 demonstrated that there were missed HIV diagnoses in 76 patients who visited an urban academic ED (n = 70), an urban community ED (n = 9), and a suburban ED (n = 4) in the year prior to diagnosis. Another study performed by Czarnogorski et al 62 demonstrated the prevalence of HIV to be 2.74 times higher (95% CI 1.…”
Section: Self-perceived Hiv Risk In Lower-risk Patientsmentioning
confidence: 99%
“…5 Institution of the CDC recommendation in Emergency Departments (ED) has been limited and, in many cases, persons with HIV are diagnosed only after several visits to the ED. [6][7][8] Even in New York State, where voluntary HIV testing is mandated, only 65% of their EDs offer testing to all patients between the ages of 13-64. 9 The ED remains an important venue for HIV testing because 17% of adults only access health care through the ED.…”
Section: Introductionmentioning
confidence: 99%